2012
DOI: 10.3382/ps.2011-01992
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical verification of a loop-mediated isothermal amplification method for detection of Salmonella species in suspect infected ducks

Abstract: To detect Salmonella spp. in suspect infected ducks, a loop-mediated isothermal amplification (LAMP) assay was developed. With the help of this assay, we can detect Salmonella enterica serovar Enteriditis and Salmonella enterica serovar Anatis above 6.0 cfu/test and 4.8 cfu/test, respectively, in pure-culture conditions, even in the existence of 0.01 g of duck liver or spleen homogenates; the detection thresholds were still achieved at 6.0 cfu per test tube. Further experiments of the test strains indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…indicating that LAMP was 10 times more sensitive than PCR in their experiment. The findings are similar with Tang et al, (2012), Zhang et al, (2012) and Wang and Wang et al, (2013) who reported the sensitivity of LAMP assay 10 times higher than the PCR-based method. The results are also in accordance with Abdullah et al, (2014) who reported that LAMP method was highly specific and 10 times more sensitive in detecting S. typhi as compared to the optimized conventional PCR method.…”
Section: Analysis Of Field Samplessupporting
confidence: 80%
“…indicating that LAMP was 10 times more sensitive than PCR in their experiment. The findings are similar with Tang et al, (2012), Zhang et al, (2012) and Wang and Wang et al, (2013) who reported the sensitivity of LAMP assay 10 times higher than the PCR-based method. The results are also in accordance with Abdullah et al, (2014) who reported that LAMP method was highly specific and 10 times more sensitive in detecting S. typhi as compared to the optimized conventional PCR method.…”
Section: Analysis Of Field Samplessupporting
confidence: 80%
“…; Tang et al . ), to our knowledge, this is the first report to directly detect Salmonella in the faecal samples free of pre‐enrichment.…”
Section: Resultsmentioning
confidence: 71%
“…While the established LAMP methods have been used to detect Salmonella in different food matrices (Hara-Kudo et al 2005;Okamura et al 2008;Li et al 2009;Ueda and Kuwabara 2009;Chen et al 2011;Tang et al 2012), to our knowledge, this is the first report to directly detect Salmonella in the faecal samples free of pre-enrichment.…”
Section: Sensitivity Of Lamp Assaymentioning
confidence: 94%
“…LAMP assay have been applied to eggs [2,14] and pork [19] to detect the Salmonella spp. The detection limit of Salmonella targeting rfbJ and fim Y was 10 3 CFU/mL in previous reports [15,18] which was lower than that of our LAMP assay. However, the reaction time was 60 min in a previous report [15], whereas the reaction time in this study was 30 min.…”
mentioning
confidence: 56%